PENGARUH LATIHAN BEBAN PADA LANSIA TERHADAP KADAR TNF-Î± - Kilapong, Russell B. J. D.; Supit, Siantan; Rampengan, J. J. V. (e-Biomedik, 2015)
Abstract: In elderly, the biological function of the systems in human body will decrease. Physical exercise is a systematical and programmed exercise to increase the body function and skills. Overtraining will influence the inflammatory response marked by the release of proinflammatory cytokines inter alia TNF-Î±. This was an experimental study with a post test design. Respondents were elderly in Panti Werdha Bethania Lembean trained for physical exercise by using dumbbells of 1-2 kg for 10-15 minutes, 3 times a week. Of 25 respondents, before the physical exercise there were 4 respondents with TNF-Î± above normal level (>100 pg/ml) and 21 respondents within normal level (10-100 pg/ml). After the 5-week physical exercise, there were 21 respondents with decreased TNF-Î± level and 4 respondents with increased TNF-Î± level. Moreover, there were no elderly with TNF-Î± level <10 pg/ml before and after physical exercise. Conclusion: Among elderly in Panti Werdha Bethania Lembean the averages of TNF-Î± level before and after physical training were within normal limit. However, there was a decrease of the average level of TNF-Î± after physical training.Keywords: physical training, elderly, TNF-Î±Abstrak: Pada lanjut usia (lansia), setiap individu akan mengalami penurunan fungsi biologis dari berbagai sistem dalam tubuh. Latihan fisik merupakan suatu aktivitas yang dilakukan secara sistematis dan terencana dalam meningkatkan fungsional tubuh dan keterampilan. Latihan olahraga berat akan merangsang respon inflamasi yang ditandai dengan pelepasan sitokin pro-inflamasi antara lain TNF-Î±. Penelitian ini bersifat eksperimental dengan rancangan post test design. Penelitian dilakukan terhadap lansia di Panti Werdha Bethania Lembean selama 5 minggu. Latihan beban 1-2 kg selama 10-15 menit dilakukan 3 kali seminggu. Dari 25 responden, sebelum latihan beban terdapat 4 orang dengan kadar TNF-Î± di atas batas normal (>100 pg/ml) dan 21 orang dalam batas normal (10-100 pg/ml). Setelah melakukan latihan beban terdapat 21 responden dengan penurunan kadar TNF-Î± dan 4 responden dengan kenaikan kadar TNF-Î±. Sebelum dan sesudah latihan beban tidak terdapat responden dengan kadar TNF-Î± <10 pg/ml. Simpulan: Pada lansia Panti Werdha Bethania Lembean rerata kadar TNF-Î± sebelum dan sesudah latihan beban masih dalam batas normal. Walaupun demikian, terdapat penurunan rerata kadar TNF-Î± sesudah latihan beban.Kata kunci: latihan beban, lansia, TNF-Î±